Brasidas in the Megarian Operation of 424 BC in the Accounts of Thucydides and Diodorus Siculus - Sinitsyn, Alexander A. (Anabasis. Studia Classica et Orientalia, 2015)
By collating the accounts given by Thucydides and Diodorus of the στάσις in Megaris in the summer of 424 BC, the article analyses Brasidas’s actions during the frustrated attack on Megara; it specifies the strength of the defence put up by the Spartan general in this operation, attempts to explain the causes of his return to the Corinthian area after he had helped the Megarians out of their predicament. Loosely based on Thucydides’ account of these events, Diodorus’ account contains digressions from the original text. Diodorus must have upheld the established tradition associated with the legendary Spartan general, so the victory at Megaris, according to Diodorus, was easily won. The article discusses the question of the whereabouts of the Helots, mustered by Brasidas for the already planned march on Chalcidice.